Pengaruh Budaya Organisasi dan Komunikasi Terhadap Kinerja Karyawan Bagian Produksi PT Karya Sekawan - Mochamad Rifan Nurhidayat; H. Cece Rakhmat; Arga Sutrisna (CV. ULIL ALBAB CORP, 2023)
This study aims to determine the effect simultaneously and partially of Organizational Culture, Comunication, Employee Perfomance in PT Karya Sekawan Tasikmalaya City. The method used in this research is method a survey. The research data were obtained by distributing questionnaires to 92 respondents. Data analysis in this study used multiple regression analysis using SPSS software. The results of this study indicate that the Organizational Culture, Comunicatio simultaneously have a significant effect on Employee Perfomance. Organizational Culture partially significant effect Employee Perfomance. Comunication has a significant effect on Employee Perfomance.